Philosophy and Practice of Education for Sustainable Development in Ukraine: On the Example of Secondary Education in the Dnipropetrovsk Region - Vysotska, Olha; Rieznikov, Serhii; Rohova, Elena; Vysotskyi, Oleksandr; Vatkovska, Maryna (European Journal of Sustainable Development, 2021)
The article reveals the features of introducing education for sustainable development in Ukraine, its theoretical basis and practical implementation on the example of Secondary Education in the Dnipropetrovsk region. The importance of forming an integrated developing educational environment based on the principles of education for sustainable development is proved. It determines the interdisciplinarity of the content of education for sustainable development, its high potential in creating a new type of educational environment. Methods and approaches of forming the values of sustainable development as important components of the development of life competencies of the individual are revealed.